1993
DOI: 10.1128/aac.37.10.2179
|View full text |Cite
|
Sign up to set email alerts
|

Drug features that contribute to the activity of quinolones against mammalian topoisomerase II and cultured cells: correlation between enhancement of enzyme-mediated DNA cleavage in vitro and cytotoxic potential

Abstract: ). However, the features of the drug that contribute to its activity towards mammalian systems have not been characterized. Therefore, CP-115,953 and a series of related quinolones were examined for their activity against calf thymus topoisomerase H and cultured mammalian cells. CP-115,953 stimulated DNA cleavage mediated by the type H enzyme with a potency that was -600-fold greater than that of the antimicrobial quinolone ciprofloxacin and -50-fold greater than that of the antineoplastic drug etoposide. As d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 36 publications
(45 reference statements)
2
70
0
Order By: Relevance
“…Quinolones, such as CP-115,953, are the only drugs that show high activity against eukaryotic and prokaryotic type II enzymes [101,[122][123][124][125]. While this last drug class has not yet been exploited to treat cancer, quinolones such as ciprofloxacin and levofloxacin that target bacterial type II topoisomerases are the most active and broad-spectrum oral antibacterials in clinical use [124,126,127].…”
Section: Non-covalent Topoisomerase II Poisonsmentioning
confidence: 99%
“…Quinolones, such as CP-115,953, are the only drugs that show high activity against eukaryotic and prokaryotic type II enzymes [101,[122][123][124][125]. While this last drug class has not yet been exploited to treat cancer, quinolones such as ciprofloxacin and levofloxacin that target bacterial type II topoisomerases are the most active and broad-spectrum oral antibacterials in clinical use [124,126,127].…”
Section: Non-covalent Topoisomerase II Poisonsmentioning
confidence: 99%
“…Furthermore, in both cases, the 4′-OH groups are essential for drug action (91,92). Thus, this group may play equivalent roles across a spectrum of topoisomerase II poisons.…”
Section: Role Of the 5-oh And 4′-oh Groups In Mediating Isoflavonementioning
confidence: 99%
“…Recently, it has been shown that 6,8-difluoro-7-(4Ј-hydroxyphenyl)-1-cyclopropyl-4-quinolone-3-carboxylic acid (CP-115, 953), a fluoroquinolone closely related to ciprofloxacin, is highly toxic to mammalian cells in culture (11,12). Studies in yeast demonstrated that top2 is the primary physiological target for this quinolone (13).…”
Section: A Sermentioning
confidence: 99%